ANALISIS KETERAMPILAN MEMBACA SISWA DENGAN MENGGUNAKAN MEDIA GAMBAR SERI PADA MATA PELAJARAN BAHASA INDONESIA - Amiruddin, Ahmad Faishol; Nanang Khoirul Umam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to help teachers train students' skills to be able to master good and correct language. The research subjects were 13 class I students at MI Sultan Agung for the 2024/2025 academic year. The data collection techniques used were observation and interviews. The instruments used were interview sheets and reading skills assessment sheets. The collected data was analyzed using descriptive quantitative techniques. The results of the research showed that using series of image media, the reading skills of class I students at MI Sultan Agung were in the very good category of 8 students or 61%, the good category of 4 students or 31%, the fairly good category of 1 student or 8%, the poor category either 0 students or 0%. The results of observations show that students have been able to master reading skills.